In vitro activity of thiamphenicol against Haemophilus influenzae, Streptococcus pneumoniae and Streptococcus pyogenes clinical isolates - Ivanchik N.V.; Sukhorukova M.V.; Chagaryan A.N.; Trushin I.V.; Dekhnich A.V.; Kozlov R.S. (Клиническая микробиология и антимикробная химиотерапия, 2021)
Objective.